Optimalisasi Pendidikan Islam Dalam Meningkatkan Kesejahteraan Mental Serta Mengurangi Burnout di Kalangan Pelajar - Agustin, Maulid; Hidayah, Ulil (LP2M Universitas Islam Ahmad Dahlan, 2024)
Islamic education has an important role to play in improving mental well-being and reducing burnout among students. Burnout, which is characterized by emotional exhaustion, depersonalization and decreased personal achievement, is often caused by academic pressure and lack of social support. This research uses the literature study method to collect and analyze information related to optimizing Islamic education in the context of mental well-being and reducing burnout among students. Islamic education emphasizes spiritual and moral values, such as empathy, patience, gratitude and tawakkal, which can help students manage stress and build positive social relationships. With a holistic approach that integrates mental health programs into the school culture, such as mindfulness practices and peer support, Islamic education can create a supportive learning environment. In addition, the concepts of destiny, qadha and qadar in Islam provide a deep understanding of life and the challenges faced. This research used the literature study method to analyze related information, and found that the integration of Islamic values in the education curriculum can prevent burnout and improve students' mental health. Social support from parents, teachers and the community also contributes to mental wellbeing, resulting in a resilient generation that contributes positively to society.